KESIAPAN GURU TERHADAP PELAKSANAAN KURIKULUM 2013 DALAM PERSPEKTIF GURU DAN SISWA PROGRAM STUDI KEAHLIAN TATA BOGA SEKOLAH MENENGAH KEJURUAN NEGERI 4 YOGYAKARTA - Dwi Mifta Rahmawati; Yasmi Teni Susiati (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
Twas to describe the teachers’ readiness in implementing 2013 curriculum at state vocational high school 4 Yogyakarta.  The type of this descriptive and quantitative research. To collect the data, the researcher used questionnaires and observation guideline. To analyze the data, the researcher used descriptive analysis through mean, median, mode, and deviation standard. This study shows that the readiness in implementing 2013 curriculum according to the teacher was in high category with the percentage 44.44% and according to the students was in enough category with the percentage 46.97%. The teachers’ readiness in implementing 2013 curriculum can be seen from four indicators; pedagogic, professional, personality, and social. According to the teachers, pedagogic indicator was in high category with the percentage 55.56% and according to the students was in high category with the percentage 63.64%. According to the teachers, professional indicator was enough category with the percentage 43.94% and according to the students was in high category with the percentage 43.94%. According to the teachers, personality indicator was in high category with the percentage 50% and according to the teacher was in enough category with the percentage 54.55%. According to the teacher, social indicator was in high category with the percentage 61.11% and according to the students was in enough category with the percentage 54.55%.